Study on Flow Boiling Characteristics in Rectangle Channel After Formation of Blisters - Huang, Huijian; Chen, Chong; Liu, Luguo; Liu, Yu; Li, Linfeng; Yu, Hao; Wang, Mingjun; Qiu, Suizheng (Frontiers in Energy Research, 2021)
Plate-type fuel elements is one of the first fuel structure choice for the novel integrated PWR, however, blisters will appear on the cladding induced by irradiation and fission. In this work CFD method was used to investigate the subcooled boiling characteristic of the water in rectangle channel with round and pillow blisters, the modified RPI model was also proposed, we can draw conclusions as follows: In the channel with round blister, as the blisters will increase the local flow resistance and more fluid will flow through center of the channel. Boiling occurred only in the area near the edges, nearly no vapor appeared at the center of the channel. The boiling region in channel with pillow shape blisters is wider and concentrated between two pillow blisters and downstream of the non-blisters side. The dry out area are both in the downstream region of blisters for the two types of channels.